Ant Colony Optimization Method and Split-Delivery Vehicle Routing Problem - Andrej Chu (Communications - Scientific letters of the University of Zilina, 2009)
This paper deals with a split delivery vehicle routing problem, which is a modification of a vehicle routing problem. It consists in delivery routes optimization in communications network containing initial city of all routes and a given number of places, which is necessary to include in delivery routes, where a customer can be served by more than one vehicle. The objective is to find a set of vehicle routes that serve all the customers and the total distance traveled is minimized. The split delivery vehicle routing problem is NP hard, therefore we present a solution approach by three heuristics, and a metaheuristics called Ant colony optimization (ACO).